Molecular and crystal structures of mesomorphic aromatic esters. II. Structure of nethoxyphenyl-n'-pentylbenzoate - O. V. Noskova; A. V. Churakov; L. G. Kuzmina; J. A.K. Howard; L. Yu. Alikberova; S. M. Pestov (Тонкие химические технологии, 2006)
n-Ethoxyphenyl-n'-pentylbenzoate was studied by X-ray diffraction analysis at 120.0 and 296.0 K. We have got any information in mutual orientation of the benzene rings and their possible conjugation the carboxy group COO, and orientation of the nearest benzene rings